TEKNIK SISTEM SIMULASI TERMAL BANGUNAN DENGAN MENGGUNAKAN PERANGKAT COMPUTATING FLUID DYNAMIC (CFD) - Tahang Tahang (Universitas Fajar, 2016)
Continuous aeration in the tropics to the main function room cooling naturally in improving the indoor climate, air movement and control that will deliver the best refreshment. The flow of air inside the building is not only influenced by the wind speed but supported by the architectural aspect. Getting the proper air flow patterns to the room as well as the controlling will depend on the performance of building ventilation which then can be a factor for good or bad, depending on the location of the building ventilation varied by using simulation method, which affect thermal comfort penghuni. Penelitian discusses thermal simulation techniques building flats on the behavior patterns of airflow and performance effective ventilation system simulation techniques software device Computating Fluid Dynamic (CFD) in some residential space in the flats Mariso in Makassar. Mechanical simulation performed to study the rate of air distribution pattern and obtain the optimal design model then completed with the parameters according to the actual conditions then iterated until it reaches convergenitas. Conclusions derived from the results of the display contours, velocity vector, or a stream of particles in the simulation results